'It can't be zero!' Difficulties in completing patient global assessment in rheumatoid arthritis: a mixed methods study. (10th October 2019) - Ferreira, Ricardo J O; de Wit, Maarten; Henriques, Marta; Pinto, Ana F; Duarte, Cátia; Mateus, Elsa; Mendes, Gabriel; da Silva, José A P; Ndosi, Mwidimi
Abstract: Objectives: Patient global assessment (PGA) is purported to add the patient's perspective in the composite measures of RA. However, PGA is not standardized and it is not known whether patients' interpretation of the measure is consistent with its intended purpose. This study aimed to explore difficulties experienced by patients with RA in completing PGA, and to assess the impact of a structured explanation in improving its validity and reliability. Methods: This was a mixed methods study, using interviews, focus groups and PGA data. During interviews, patients (convenience sample, n = 33) completed three often-used PGA formulations. Then a nurse provided structured explanation about what PGA is and why it is used. After further discussion, patients completed one PGA version again. Interviews were recorded, transcribed and analysed using inductive thematic analysis. We compared PGA scores pre- and post-explanation (Wilcoxon signed-ranks) and the proportion of patients achieving RA remission with PGA ⩽1 (McNemar's tests). Results: Three themes emerged: understanding the meaning of PGA, the purpose of PGA and measurement difficulties. The difficulties caused systematic errors in PGA completion such as marking higher when feeling well, marking near the centre or away from zero. The structured explanation was helpful. Following the explanation, the median PGA score decreased from 3.0 to 2.1 cm, and the proportion of non-remission solely due to PGA >1 from 52% to 41%; none of these changes was statistically significant. Conclusion: Many patients have difficulties in completing PGA. Standardization of PGA and a structured explanation may improve its clarity, validity and reliability.